Work Motivation As A Mediator Of The Influence Of Employee Competence And Democratic Leadership Style On The Performance Of Employees Of The Mojokerto City Regional Secretariat Office - Farida, Siti Juni; Nasir, M. Jamal Abdul; Farhan, Djuni (International Journal Labs, 2024)
This study aims to analyze the influence of: (1) employee competence on work motivation, 2) democratic leadership style on work motivation , (3) employee competence on employee performance, (4) democratic leadership style on employee performance, (5) work motivation on employee performance, (6) employee competence on employee performance through work motivation, (7) democratic leadership style to employee performance through work motivation. Using an explanatory research approach, this research was conducted at the Mojokerto City Regional Secretariat Office in April-August 2023. The population is 108 civil servants in the Office. The sample was determined by saturated/census sampling technique of 108 people (excluding the author). Primary data related to research variables were obtained by giving questionnaires directly to respondents. Once the data is collected, it is analyzed using Warp PLS 8. However, validity and reliability tests were previously carried out. The results of this study prove that: (1) employee competence has a significant positive effect on work motivation, (2) democratic leadership style has a significant positive effect on work motivation, (3) employee competence has a significant positive effect on employee performance, (4) democratic leadership style has a significant positive effect on employee performance, (5) work motivation has a significant positive effect on employee performance, (6) work motivation Unable to increase the influence of employee competence on employee performance, (7) Work motivation is unable to increase the influence of democratic leadership style on employee performance.